Analysis of Potential Visitors' Preferences for Tourism Website Interface Design: A Case Study of The Empat Lawang Tourism Office Website - Alexander, Onki; Salamah, Ummy Gusti; Purwanto, Heru; Leonaldo, Ocin; Fawzi, Fiddini Sharika (Green Publisher Indonesia, 2025)
This study investigates potential visitors’ preferences in tourism website interface design, focusing on the case of the Tourism Office website of Empat Lawang Regency. The research adopts a mixed-methods approach combining user surveys, heuristic evaluation, and usability testing to identify key interface elements influencing user experience. Findings reveal that visitors prioritize intuitive navigation, responsive design, and visually appealing content. Additionally, access speed, multi-device compatibility, and structured information significantly impact satisfaction. Unlike prior studies that center on developer-driven design, this research introduces a user-centered design perspective grounded in empirical user preferences. This shift underscores the importance of aligning design strategies with actual visitor expectations. The novelty of this work lies in its contextual application of UX principles in a regional tourism setting, offering localized design insights often overlooked in mainstream studies. The study contributes actionable design recommendations aimed at improving website usability, increasing tourist engagement, and enhancing the digital image of emerging tourist destinations like Empat Lawang.